2006
DOI: 10.1001/archsurg.141.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Meperidine Use in Older Surgical Patients

Abstract: The unique toxic and adverse effects of meperidine hydrochloride have prompted a number of expert panels convened by national health care policy organizations to recommend that meperidine not be used in older patients. We hypothesized that the prescription of meperidine was less likely to reflect these recommendations in older surgical patients than in older medical patients. The current study examined the use of meperidine in 2 urban hospitals as 1 quality indicator of the care of older adults, measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Variation in PIM use according to physician specialty has also been documented in participants admitted with medical diagnoses because cardiologists and internists are more likely to prescribe PIMS than geriatricians 10 . Smaller studies examining meperidine use in hospitalized people aged 65 and older found that those undergoing surgery were seven times as likely as medical patients to receive meperidine 15 …”
Section: Discussionmentioning
confidence: 99%
“…Variation in PIM use according to physician specialty has also been documented in participants admitted with medical diagnoses because cardiologists and internists are more likely to prescribe PIMS than geriatricians 10 . Smaller studies examining meperidine use in hospitalized people aged 65 and older found that those undergoing surgery were seven times as likely as medical patients to receive meperidine 15 …”
Section: Discussionmentioning
confidence: 99%
“…A population-based study indicated that patients aged 80 years and older who received care in clinics tended to be prescribed potentially inappropriate medications (30). Previous studies also reported that pethidine was administered to only approximately one in eigth older surgical patients (10), mainly due to the greater likelihood that the elderly would experience side effects from pethidine, which may have affected physician prescribing behavior (31). The increased number and proportion of elderly pethidine users in recent years noted in our study warrants further intervention to effectively reduce the use of pethidine in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Valano et al (29) used a cross-sectional study design to demonstrate that adherence to analgesic treatment guidelines was higher in large hospitals than in medium- and small-sized hospitals. A recent study also reported that pethidine was prescribed to 7.6% and 4.3% of all study patients at a large private tertiary care teaching hospital and a smaller academically affiliated Veteran's Affairs medical center, respectively, but the number of doses administered was similar at both sites (10). The variation in the number of pethidine doses prescribed to patients treated in hospitals with different accreditation levels may reflect the different severity of diseases that required different strategies to manage pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the wealth of documentation in the primary literature outlining the dangers of meperidine, it continues to be prescribed as a first-line agent, particularly by surgeons. 1 We outline two different approaches to meeting this challenge, both of which were implemented at the Memorial Healthcare System, a 1300-bed, four-hospital system in Fort Lauderdale, Florida.…”
mentioning
confidence: 99%